Pakistan : Tenth Review Under the Extended Arrangement and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Pakistan. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses economic performance status and policy developments of Pakistan. Amid setbacks to structural reform, the authorities have made substantial progress in restoring economic stability. Economic activity continues to strengthen gradually. International reserve buffers are increasing amid a broadly stable current account deficit. However, there are number of risks to the economy. Slower growth in key advanced markets such as China and the Gulf can further erode export competiveness. The Pakistani government is determined to maintain fiscal consolidation in FY 2015/16 and over the medium term. Continued tax administration reforms are important for further improving tax compliance and supporting revenue mobilization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet